How feasible is human resource accounting in Libyan commercial banks A field study on commercial banks in the city of Zawiya (Comprehensive Journal of Science, 2026)
This study aimed to investigate the feasibility of implementing Human Resource Accounting (HRA) in Libyan commercial banks within the city of Zawiya. This was achieved by assessing the levels of awareness and perception, the availability of necessary requirements, and identifying the constraints hindering its application. The study adopted a descriptive-analytical approach, analyzing data from (86) questionnaires using the Statistical Package for the Social Sciences (SPSS v.27).The results, derived from the One-Sample T-Test and effect size (Cohen's d), led to the acceptance of the main hypothesis with a grand mean of (3.95), confirming a substantial practical feasibility for implementation. Key findings highlighted a very high level of awareness regarding the system's importance and a high degree of technical and financial readiness, while the absence of unified professional standards emerged as the most significant barrier. The study recommended that the Central Bank of Libya and professional regulatory bodies issue a unified accounting manual to standardize the measurement and disclosure of human resources as a strategic asset, and to initiate the capitalization of training and promotion expenditures within the financial statements.
Keywords: Human Resource Accounting (HRA), Libyan Commercial Banks, Human Assets, Accounting Measurement and Disclosure, Libyan Professional Environment.